2022
DOI: 10.1177/1759720x221124028
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model to identify multiple failure to biological therapy in patients with rheumatoid arthritis

Abstract: Background: Despite advances in the treatment of rheumatoid arthritis (RA) and the wide range of therapies available, there is a percentage of patients whose treatment presents a challenge for clinicians due to lack of response to multiple biologic and target-specific disease-modifying antirheumatic drugs (b/tsDMARDs). Objective: To develop and validate an algorithm to predict multiple failure to biological therapy in patients with RA. Design: Observational retrospective study involving subjects from a cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…of disease activity through the measurement of cytokines (36) and multirefractory and non-refractory patients by using simple measurements recorded in routine clinical practice for individual treatment protocols in an early stage of RA (37). Studies have shown that irregular dental attendance at a late stage of primary school and high levels of salivary S.mutans and male sex at an early stage of primary school are associated with a higher risk of dental caries (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of disease activity through the measurement of cytokines (36) and multirefractory and non-refractory patients by using simple measurements recorded in routine clinical practice for individual treatment protocols in an early stage of RA (37). Studies have shown that irregular dental attendance at a late stage of primary school and high levels of salivary S.mutans and male sex at an early stage of primary school are associated with a higher risk of dental caries (38).…”
Section: Discussionmentioning
confidence: 99%
“…It chooses the "best" characteristics to partition the data into specific classes (34,35). This method has been used to predict disease activity (36) and treatment response in rheumatoid arthritis (RA) (37) as well as to identify a high risk group for dental caries in school children (38). The Classification and Regression Tree (CART) algorithm, a type of DTA, has been used to develop a diagnostic algorithm for BS uveitis (39) and to predict relapse in intestinal BS (40).…”
Section: Introductionmentioning
confidence: 99%
“…The use of this composite index during the early stages of treatment with b/tsDMARDs provides an objective measurement that is able to not only predict the outcome of multidrug failure, but also to discriminate between D2TRA-inefficacy patients vs good responders. 15 …”
Section: Discussionmentioning
confidence: 99%
“…The use of this composite index during the early stages of treatment with b/tsDMARDs provides an objective measurement that is able to not only predict the outcome of multidrug failure, but also to discriminate between D2TRA-inefficacy patients vs good responders. 15 With regard to our previous data, 7 15 in this study we have modified the inclusion criteria for the NoD2TRA group, including those patients who responded well to the first b/tsDMARD and those who failed a line of treatment, but who did not meet the D2TRA definition. Likewise, by using a different statistical model, we corroborated that DAS28 is a robust classification measure for assessing multiple drug failure, taking into account these subgroups of patients.…”
Section: Rmd Open Rmd Open Rmd Openmentioning
confidence: 99%
“…ML algorithms have demonstrated efficacy in enhancing the precision of response prediction for TNF inhibitors and MTX. Furthermore, ML methodologies are being increasingly utilized in forecasting treatment responses to a range of other biologic therapies ( 61 64 ). Clinical data may be limited by trial design, including inclusion and exclusion criteria.Using deep learning technology for cluster analysis on RA patients has revealed the connection between patient characteristics and treatment response ( 105 ).…”
Section: Models In Precision Diagnosis and Therapeutics For Ramentioning
confidence: 99%